The Influence of Product Quality, Online Shopping Experience and Price Fairness on Consumer Loyalty at Skintific Skincare in Padang City with Customer Satisfaction as a Mediating Variable - Mawaddah Laura, Al; Thaib, Ilham (International Journal of Economics and Management Research, 2024)
This study aims to analyze the influence of Product Quality, Online Shopping Experience, and Price Fairness on Consumer Loyalty, with Customer Satisfaction as a mediating variable, among users of Skintific skincare products in Padang City. The growing trend of skincare product usage and the increasing frequency of transactions through e-commerce highlights the importance of understanding the factors influencing consumer loyalty, particularly within the context of intense competition in the beauty industry. A quantitative approach was employed using a survey method and purposive sampling technique. The sample consisted of 160 respondents who were active users of Skintific products, aged 18–35 years, and residing in Padang City. Data processing and analysis were conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) statistical tool with the assistance of SmartPLS 4.0 software. The results indicate that both Product Quality and Online Shopping Experience have a positive and significant effect on Consumer Loyalty, either directly or through the mediation of Customer Satisfaction. However, Price Fairness was found to have no significant influence on Consumer Loyalty, either directly or indirectly through Customer Satisfaction. Overall, Customer Satisfaction was proven to be a significant mediating variable that strengthens the influence of the independent variables on consumer loyalty. The implications of this study suggest that Skintific should focus on improving product quality and online shopping experiences, as well as considering fair price perceptions, to maintain and enhance consumer loyalty in an increasingly competitive skincare market